PREPARATION OF fROM SMOKE CURED OIL SARDINE FILLETS - MURALEEDHARAN, V; VALSAN, A P (Fishery Technology, 2017)
A method of preparation of smoke cured filletsof oil sardine is described. Various procedural stepslike brining, smoking, packaging etc. have been described andthe shelf life assessed. Sodium propionate treatment is recommendedto ehnance storage life; BHA to control rancidity;and thermal treatment to overcome the insect infestation. Theproduct has good consumer appeal.